What is the true value of fertilizer? An assessment of farmers willingness-to-pay for fertilizers across the hill and Terai regions of Nepal - Ward, Patrick S.; Gupta, Shweta; Singh, Vartika; Gautam, Shriniwas; Guerena, David; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2019)
Agriculture in Nepal has historically suffered from low levels of productivity. Inadequate usage of fertilizer, poor fertilizer quality, and insufficient supply to satisfy demand have been identified among the major reasons behind this low productivity (Joshi, 2010). Other factors such as land fragmentation, lack of irrigation, lack of good quality seeds, inadequate public investment and more recently climate change (e.g., Niroula & Thapa; Joshi et al., 2012; Ghimire et al., 2015; Malla, 2008) also remain as challenges for Nepalese agriculture. Both the Agriculture Perspective Plan (APP, 1994-2014) and the Agriculture Development Strategy (ADS, 2015-2034) have recognized the deficiencies in the fertilizer supply chain and have prioritized the widespread distribution and utilization of fertilizers as essential elements in their development strategies (Bista et al., 2016). With continuation of the fertilizer distribution issues, a voucher system has been proposed in the ADS (2015-2035) but is yet to be implemented. As with any type of transfer policy, proper identification of intended beneficiaries and calibration of voucher payments is critical for its successful rollout. It is therefore imperative that all concerned stakeholders including government agencies garner a more complete understanding of the true demand of chemical fertilizers to optimize policy design. Through this study, we determine the implicit value farmers place on fertilizers as well as other perennial costs associated with obtaining fertilizers, such as travel costs and certainty premia.